Jedi's Light Sabre: Site Specific Photocleavage of Proteins with Light - Buranaprapuk, Apinya; V. Kumar, Challa (Science Essence Journal, 2018)
ABSTRACT The ability of photoreagent to target and photocleave the protein backbone at a single site has been a considerable challenge for over decades. The structure of the photoreagent can be systematically modified to provide valuable information on the binding site recognition and photoreaction mechanisms. Many factors, for example, functional groups and overall charge present on the probe, conformations of the bound probe, protein size and amino acids present at the binding site, can affect the photocleavage reaction. A variety of spectroscopic methods (absorption, fluorescence and circular dichroism spectroscopies) were used to monitor the binding interaction. Peptide bond cleavage reactions were obtained from irradiation, at the probe absorption wavelength (~340 nm), of the probe/protein mixture, in the presence of an electron sink. The mechanism indicated the important role of aromatic cation radicals in the mechanistic path as obtained from laser flash photolysis studies. Computer docking studies can be used to provide strong support for the photocleavage and sequencing studies. The docked structures indicated the location of the probe in good proximity to the obtained cleavage site. In this short review, we focused mainly on few generic proteins, such as serum albumin, lysozyme and avidin. However, this strategy may be extended to other proteins with appropriate modifications, which could be useful in a rational design of novel photoreagents to target desired sites on proteins in future studies.